Pelabuhan Penumpang Selat Lampa Di Natuna Sebagai Destinasi Wisata - Fachry Enzeta; Pedia Aldy; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lampa Strait Passenger Harbour in Natuna is a transportation amenities connecting Natuna Island with its surrounding area. The terminal building is unavailable in existing harbour. This design background is the increase of passengers and good tourism potential. The design of Lampa Strait Passenger Harbour do by combining the harbour function as a node of sea transportation network with tourism as an attraction to bring tourists as well as utilizing the harbour as a destination. The concept use in this design is sparkling in the ocean. This design is expected to accommodate tourism and transportation activities. The application concept in the design of Lampa Strait Passenger Harbour is in transportation and tourism activities that will be supporting each other which includes on the zone function between tourism and harbour, the vegetation, the circulation, the interior order, the outdoor space arrangement, form of the mass come from the result of design concepts elaboration, mass arrangements on interconnected treads, convenient utilities for users, building facades, and landscape arrangement, all of these aplication is to attract the tourist curiosity and passenger comfort.Keywords: Passenger Harbour, Transportation, Tourism